Gender mainstreaming: A strategic approach - Margo Thomas; César Córdova-Novion; Arjan de Haan; Gimena de León; Maxime Forest; Sandhya S. Iyer (Kiel Institute for the World Economy (IfW), 2018)
As a starting point, this paper recognizes the importance of gender equity for economic growth, societal well-being, and sustainable development. Moreover, the paper acknowledges that while women make up half of the world's population, most policy, program and government initiatives affect women and men differently. To address gaps in policies, implementation and impacts the authors propose a strategic approach to gender mainstreaming that strengthens inclusive policy making by adding a gender lens and tools for assessing the impact of policies on women and other under-represented groups and targets the determinants of gender inequity, based on three pillars: systematic reviews of policies, laws and regulations that limit women's economic activity; gender budgeting; and improving the quality of gender disaggregated data to support impact assessments, policy analyses, and advocacy. The commitment of the Argentine presidency to fostering a gender mainstreaming strategy across the whole G20 agenda and boosting "women's empowerment, the elimination of gender disparities in employment, science, technology and education, and protection from all forms of gender-based violence." provides an opportunity for bringing this issue forward for the 2018 G20.
Keywords: E61; H61; 330; budgeting; economic empowerment; gender; gender equity; impact assessments; mainstreaming; policy; process